The effect of waterlase laser and herbal alternative, green tea and Salvadora Persica (Siwak) extract on push-out bond strength - Al-Azzawi, Abdul kareem J (Journal of Baghdad College of Dentistry, 2014)
Background: The bond strength of root canal sealers to dentin was important for maintaining the integrity of the seal in root canal filling in both static and dynamic situations. In a static situation, it should eliminate any space that allowed the percolation of fluids between the filling and the wall while in a dynamic situation; it was needed to resist dislodgement of the filling during subsequent manipulation. Materials and Methods: Forty mandibular premolars were selected for this study. All canals were instrumented using ProTaper rotary instruments. Instrumentation was done with copious irrigation of 5.25% sodium hypochlorite. Roots were randomly divided into four groups according to the type of cleaning and method of root canal irrigation (ten teeth for each group): Group A. The root canals were irrigated with 5 ml of 17% of EDTA for 1 minute and 5 ml of 5.25% NaOCl. Group B. Cleaning with waterlase laser. Group C. The root canals were irrigated with 5 ml of 5mg/ml of siwak (Salvadora persica) extract for one minute. Group D. The root canals were irrigated with 5 ml of 5% of green tea (camellia sinensis) extract for one minute. All groups were rinsed with distilled water and then obturated with cold lateral condensation technique and i Root sp sealer (Bioceramic sealer, the roots then stored in moist environment at 37Â°C for one week. Three horizontal sections were prepared at a thickness of 1 mm Â±0.1 in the apical, middle and coronal parts of each root. The test specimens were subjected to the push-out test method using a Universal Test Machine that carried 1-mm, 0.5- mm and 0.3-mm plungers for coronal, middle and apical specimens, respectively. The loading speed was 0.5 mm/ min. The computer showed the higher bond force before dislodgment of the filling material. These forces were divided by the surface area to obtain the bond strength in MPa. Results: In all groups the mean value of push-out strength was greatest in apical area and least in coronal area and the middle area was in between, except in Waterlase the middle area showed the least mean push-out strength. Conclusion: Herbal extracts used in this study (Siwak and green tea) can be used safely as an intra-canal irrigant for smear layer removal with efficiency that is comparable with conventional synthetic materials (EDTA) and more complicated methods (Waterlase).